Nanomedicines Targeting the Tumor Microenvironment. Issue 4 (July 2015) - Tong, Rong; Langer, Robert
<x xml:space="preserve">Abstract</x> Abstract We review recent progress in cancer nanomedicine to overcome the delivery barriers in tumor microenvironment, including the understanding in the nanomedicine delivery process, stimulus-responsive delivery, and several new strategies to normalize tumor microenvironment. The application of nanomedicine in cancer immunotherapy, a renewed cancer therapy by recent breakthrough, is also highlighted.